2023
DOI: 10.1186/s12960-022-00782-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of doctor allocation policies on the equitable distribution of doctors in Thailand

Abstract: Background Equitable geographic distribution of doctors is crucial for the provision of an accessible and efficient health service system. This study aimed to assess the effects of doctor allocation by the Thai Ministry of Public Health (MoPH) in relation to equity distribution. Methods This descriptive study compared secondary data on the number of doctors, gross provincial products (GPP), and populations of 76 Thai provinces for the years 2017 an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…While the Gini coefficient was initially designed to measure income distribution in the field of economics, it has also been used to measure workforce distribution. 13,14…”
Section: Discussionmentioning
confidence: 99%
“…While the Gini coefficient was initially designed to measure income distribution in the field of economics, it has also been used to measure workforce distribution. 13,14…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted January 12, 2024. ; https://doi.org/10.1101/2024.01.10.24301140 doi: medRxiv preprint evaluated by the policymakers for strategic planning to achieve 80% of UHC SCI by the year 2030. The spatial allocation of healthcare resources (23,24) with the use of SAI could be more helpful in low facility settings. One of the best evidence was provided from a Portuguese study and it demonstrated how the enhanced-2SFCA method was used to implement a new healthcare reform initiative for establishing emergency network points in a convenient distance to their residents (25).…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…Based on past literature (20,21), a deep comparison of the concentration of registered nurses in different regions of Guangdong province was conducted based on the population density. The regions were categorized into densely populated areas (PAD > 2), areas with moderate population (0.5 < PDA < 2), and sparsely populated areas (PAD < 0.5).…”
Section: Medical Resource Concentration (Hrdi)mentioning
confidence: 99%